Exosomes form tunneling nanotubes (TUNTs) in the blood-brain barrier: a nano-anatomical perspective of barrier genesis - Mentor, Shireen; Fisher, David (Frontiers in Molecular Neuroscience, 2022)
The blood-brain barrier (BBB) is a robust interface between the blood and the central nervous system. Barrier type endothelium is able to limit paracellular (PC) movement, relegating molecular flux to the transendothelial pathways of brain endothelial cells (BECs). It is, therefore, apparent that any leakage via the PC shunts would effectively nullify the regulation of molecular flux across the transcellular pathways. The application of higher-resolution scanning electron microscopy (HR-SEM) illuminates the heterogenous, morphological profile that exists on the surface of BEC membranes and the relationship between these ultrastructures during the molecular construction of the PC space between adjacent BECs. In this study developing BEC monolayers were grown on mixed, cellulose esters insert membranes in a bicameral system. BEC monolayers were fixed in 2.5% glutaraldehyde, hydrated, critically dried, and sputter-coated, for imaging utilizing HR-SEM. This study, for the first time, showed membrane-bound exosomes were attached to the plasma membrane surfaces of the BECs. The exosomes were characterized as small membrane-bound, nano-sized exosomes (30–300 nm). Based on their membrane morphology and anatomical structure, exosomes appear to possess two distinct functions, namely: paracrine secretion and nanotube construction between adjacent BECs, during in vitro barrier genesis. The HR-SEM micrographs in conjunction with the Tipifarnib inhibition of exosome formation, suggests that brain capillary endothelial exosomes play a prominent role in the bilateral signaling, which contribute to the regulation of the permeability of the BBB. Given that blood-brain barrier permeability has been implicated in the progression of many neurodegenerative pathologies, the role of these exosomes and TUNTs posits the capacity of these structures to exacerbate neuropathologies that implicate BBB permeability. These findings could lead to the development of novel treatment interventions and moreover, the characterization of BBB exosomes may be a reliable target for identifying therapeutic biomarkers in neurodegenerative disease. Conversely, the presence of BBB exosomes raises a critical enterprise to target the exosome-induced nanotubes as a vehicle for transferring therapeutic treatments across the BBB.